Comparison of Various Techniques of Anesthesia for Surgical Management of Diabetic Foot - Kapil S. Divekar; Karishma D. Mehta; Mehta, Pancham; Payal P. Prajapati; Mehta, Kamla H. (Academia Anesthesiologica International, 2020)
Background: Diabetes mellitus is a multisystem disease caused by an absolute or relative deficiency of insulin secretion or resistance or a combination of both. Anesthesia in them is of special concern because of complex polypharmacy, an inappropriate dose of oral hypoglycemic agents or insulin and errors in converting IV insulin to usual medication. The objective is to compare the various techniques of anesthesia for surgical management of diabetic foot in terms of intraoperative hemodynamic stability, perioperative problems related to anesthesia techniques, postoperative analgesia. Subjects and Methods: Sixty adult diabetic patients of both gender of ASA grade II-III, aged 35years undergoing surgical management of diabetic foot were elected and separated into three groups, Group A: general anesthesia with tracheal intubation, Group B: unilateral spinal anesthesia with injection 0.5% bupivacaine heavy 1.5ml (7.5mg), Group C: popliteal nerve block via lateral approach by injecting 30 ml 0.5% bupivacaine. Parameters like pulse rate, mean arterial blood pressure, respiratory rate and SpO2 were recorded at regular intervals. Postoperative pain, perioperative side effects, complications and problems related to anesthetic techniques were noted. The analysis is done by unpaired t-test and chi-square test. Results: Group C patients were hemodynamic stable than Group A and B. Post-op analgesia was prolonged in Group C. Perioperative side effects were more found in Group A. Conclusion: Popliteal nerve block and unilateral spinal anesthesia provide better hemodynamic stability and postoperative analgesia with negligible side effects as compared to general anesthesia for surgical management of diabetic foot.